Income Per Capita and Exports Drive Tax Revenue in ASEAN Countries: Pendapatan Per Kapita dan Ekspor Mendorong Pendapatan Pajak di Negara-Negara ASEAN - Maghfira, Chika Nanda; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Optimizing tax revenue is crucial for achieving sustainable economic growth and funding development in ASEAN countries. Specific Background: Macroeconomic factors, including Foreign Direct Investment (FDI), inflation, income per capita, and trade balance, are generally considered key determinants of a nation's tax base and revenue generation. Knowledge Gap: Existing literature shows inconsistencies regarding the sign and significance of these macroeconomic variables, particularly when assessing the role of economic growth as a potential moderator in the ASEAN context. Aims: This study aims to analyze the direct relationships between FDI, inflation, per capita income, exports, and imports with tax revenue, and to examine the moderating role of economic growth in these relationships across six ASEAN nations from 2015 to 2022. Results: Utilizing PLS-SEM, the findings indicate that per capita income and exports positively relate to tax revenue, while FDI, inflation, and imports show no direct relationship. Crucially, economic growth significantly weakens the negative association of inflation on tax revenue. Novelty: This research provides an updated, comprehensive analysis of direct and conditional macroeconomic relationships specific to the tax structure of key ASEAN economies. Implications: Policy focus should be placed on fostering higher per capita income and robust export sectors, alongside utilizing economic growth to mitigate inflationary risks to the tax system. Highlights: Per Capita Income and Exports are the significant drivers of Tax Revenue. FDI, Inflation, and Imports show no direct relationship with Tax Revenue. Economic Growth weakens the negative influence of Inflation on Tax Revenue. Keywords: Per Capita Income, Exports, Tax Revenue, Economic Growth, ASEAN